2013
DOI: 10.31274/ans_air-180814-1249
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection of Purebred Animals for Crossbred Performance in the Presence of Dominant Gene Action

Abstract: Background: Genomic selection is an appealing method to select purebreds for crossbred performance. In the case of crossbred records, single nucleotide polymorphism (SNP) effects can be estimated using an additive model or a breed-specific allele model. In most studies, additive gene action is assumed. However, dominance is the likely genetic basis of heterosis. Advantages of incorporating dominance in genomic selection were investigated in a two-way crossbreeding program for a trait with different magnitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…They differed from the parent models because they were defined using the female-and male-origin haplotypes of each progeny inferred by long-range phasing. Such models were implemented in previous studies (Ibánez-Escriche et al, 2009;Kinghorn et al, 2010;Zeng et al, 2013) while only considering additive effects in the model. We extended this approach by including dominance and epistatic effects.…”
Section: Statistical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…They differed from the parent models because they were defined using the female-and male-origin haplotypes of each progeny inferred by long-range phasing. Such models were implemented in previous studies (Ibánez-Escriche et al, 2009;Kinghorn et al, 2010;Zeng et al, 2013) while only considering additive effects in the model. We extended this approach by including dominance and epistatic effects.…”
Section: Statistical Modelmentioning
confidence: 99%
“…This is especially the case regarding animal breeding, when purebred animals are evaluated for their crossbred performance, where models that take the allele origin into account are implemented. Some rely on the relationship among purebred parents (Lo et al, 1997), which are referred to as 'parent models' in the following, while others are based on the relationship among crossbred progenies estimated by their gametotype (haplotype of each parental gamete) (Ibánez-Escriche et al, 2009;Kinghorn et al, 2010;Zeng et al, 2013), which are referred to as 'progeny models' hereafter. Although both parent and progeny models have been fully studied in assessing the performance of crossbreeds, they have mainly been focused on genetic additive effects.…”
Section: Introductionmentioning
confidence: 99%
“…In simulation studies on genomic prediction with training sets consisting of crossbred individuals (Ibánez-Escriche et al 2009;Zeng et al 2013) or single-cross hybrids (Technow et al 2012), it was found that genomic prediction models that fitted specific marker effects for the parental populations (i.e., purebred breed or heterotic group) had little or no advantage over simpler models that assumed marker effects to be the same across parental populations. One explanation the authors gave for this was that the linkage phase consistency across populations was sufficiently high at high marker densities.…”
mentioning
confidence: 99%
“…of the relevance of predicting genotypic value based on markers in animal and plant breeding. Zeng et al (2013) concluded that genomic selection based on the dominance model maximized the cumulative response to selection of purebred animals for crossbred performance.…”
Section: Discussionmentioning
confidence: 99%